The Role and Function of HDL in Patients with Chronic Kidney Disease and the Risk of Cardiovascular Disease - Rysz, Jacek (Int J Mol Sci, 2020)
Chronic kidney disease (CKD) is a worldwide health problem with steadily increasing occurrence. Significantly elevated cardiovascular morbidity and mortality have been observed in CKD. Cardiovascular diseases are the most important and frequent cause of death of CKD patients globally. The presence of CKD is related to disturbances in lipoprotein metabolism whose consequences are dyslipidemia and the accumulation of atherogenic particles. CKD not only fuels the reduction of high-density lipoprotein (HDL) cholesterol concentration, but also it modifies the composition of this lipoprotein. The key role of HDL is the participation in reverse cholesterol transport from peripheral tissues to the liver. Moreover, HDL prevents the oxidation of low-density lipoprotein (LDL) cholesterol by reactive oxygen species (ROS) and protects against the adverse effects of oxidized LDL (ox-LDL) on the endothelium. Numerous studies have demonstrated the ability of HDL to promote the production of nitric oxide (NO) by endothelial cells (ECs) and to exert antiapoptotic and anti-inflammatory effects. Increasing evidence suggests that in patients with chronic inflammatory disorders, HDLs may lose important antiatherosclerotic properties and become dysfunctional. So far, no therapeutic strategy to raise HDL, or alter the ratio of HDL subfractions, has been successful in slowing the progression of CKD or reducing cardiovascular disease in patients either with or without CKD.